Preparation for motherhood during pregnancy : A concept analysis (2017)
ABSTRACT: Objective. This work sought to identify the attributes of the concept of preparation for motherhood during pregnancy. Methods. Concept analysis with the method by Walker and Avant, which conducted a literature review in databases and other sources. Inclusion criteria were defined and a database was created with the articles included for the analysis. The information was integrated, responding to the eight steps proposed in the method. Results. The concept of preparation for motherhood during pregnancy is defined as an intermediate process of active and conscious participation defined by the cultural, social, and historical contexts, which favor lifestyle changes to optimize health and whose attributes are classified into physical and psychological preparation. Conclusion. The attributes identified contribute to understanding the preparation for motherhood during gestation as a multidimensional concept. These results could be used to design care actions to evaluate pregnant women and prescribe nursing care beyond purely biomedical issues.